Islamic Education Through the Tadzkirah Model (Example, Guide, Encouragement, Zakiyah, Continuity, Remind, Repetition, Organize, Heart) in Character Learning for Students in Elementary Schools - Lailatul Qurrota Ayuni; Asep Rudi Nurjaman (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
Character education for elementary school students is vital in shaping individuals of noble character. Islamic education emphasizes moral values based on the Qur’an and Hadith, which must be integrated into the daily learning process. The TADZKIRAH model is one Islamic framework that combines several teaching strategies (Teladan [Exemplary], Arahkan [Direct], Dorongan [Encourage], Zakiyah [Sincerity], Kontinuitas [Continuity], Ingatkan [Remind], Repetisi [Repetition], Organisasikan [Organize], Heart [Empathy]) to internalize character values. This article examines the implementation of the TADZKIRAH model in character education for elementary school students in Indonesia (both Islamic and public schools). The research method combines a review of recent literature with field observations (qualitative study). The findings indicate that applying the TADZKIRAH model can enhance students’ spiritual and moral awareness through a structured and repetitive habituation process. For example, teachers as exemplars provide demonstrations of good behavior that foster discipline and responsibility, and the consistent teaching of creed and character materials solidifies the formation of faithful character. The discussion highlights the importance of teachers’ roles, the family environment, and continuity in instilling Islamic values. In conclusion, integrating Islamic educational values through the TADZKIRAH model has been proven effective in building the character of elementary school students, and it is recommended as a formal framework in basic education.